Successful treatment with interleukin-17A antagonists of generalized pustular psoriasis in patients without IL36RN mutations - Wilsmann-Theis, Dagmar; Schnell, Lisa Marie; Ralser-Isselstein, Veronika; Bieber, Thomas; Schoen, Michael P.; Hüffmeier, Ulrike; Moessner, Rotraut (Journal of Dermatology, 2018)
Generalized pustular psoriasis (GPP) is a potentially life-threatening disease that can be attributed to mutations in IL36RN in a subgroup of patients. In small trials, interleukin (IL)-17A and IL-17RA antagonists have been shown to be effective in patients with generalized pustular psoriasis in Japan. We identified seven patients who received the IL-17A antagonists secukinumab (six cases) or ixekizumab (one case) in two dermatological centers. All patients showed a good or excellent clinical response. Anti-IL-17A therapy was well tolerated and ongoing in all patients after an average therapy duration of 12.9 months. Analysis of IL36RN mutation status was performed in six patients, one patient carried a heterozygous mutation, while the other five patients did not show a mutation in IL36RN. This is the first report of a successful treatment of GPP patients without IL36RN mutations responding to anti-IL-17A therapy.
EVALuna2:34625